2000
DOI: 10.1200/jco.2000.18.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Early Breast Cancer Patients Is Favorably Influenced by a Natural Humoral Immune Response to Polymorphic Epithelial Mucin

Abstract: Early breast cancer patients with a natural humoral response to MUC1 have a higher probability of freedom from distant failure and a better disease-specific survival. MUC1 antibodies may control hematogenic tumor dissemination and outgrowth by aiding the destruction of circulating or seeded MUC1-expressing tumor cells. Vaccination of breast cancer patients with MUC1-derived (glyco)peptides in an adjuvant setting may favorably influence the outcome of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
145
8
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(161 citation statements)
references
References 57 publications
7
145
8
1
Order By: Relevance
“…Overexpression of tumour antigens or expression of cryptic antigens following structural modification can lead to an improper immune reaction against this protein (von Mensdorff-Pouilly et al, 2000). Such a phenomenon might explain the presence of autoantibodies to endostatin in our patients; even so, endostatin may be expressed mostly by tumour-associated stromal cells.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Overexpression of tumour antigens or expression of cryptic antigens following structural modification can lead to an improper immune reaction against this protein (von Mensdorff-Pouilly et al, 2000). Such a phenomenon might explain the presence of autoantibodies to endostatin in our patients; even so, endostatin may be expressed mostly by tumour-associated stromal cells.…”
Section: Discussionmentioning
confidence: 85%
“…Autoantibodies are frequently observed in the sera of patients with malignancies and their titres have been correlated to patients' survival or other clinicopathological parameters (Soussi, 2000;von Mensdorff-Pouilly et al, 2000). Cancer-related autoimmunity often appears to be directed against mutant forms of proteins or is associated with the overexpression of autoantigens in autologous tumour cells (Boon and Old, 1997;Soussi, 2000).…”
mentioning
confidence: 99%
“…These circulating antibodies are associated with a good prognosis [17]. Moreover, a report that non-MHC-restricted cytotoxic T-cells could be isolated that recognized an epitope in the TR sequence of MUC1, which is masked in the normal mucin, suggested that cellular immune responses may also be induced [18].…”
Section: Introductionmentioning
confidence: 99%
“…5 There have been reports of humoral and cellular immune responses to MUC1 in multiparous women and in cancer patients, 6 with the presence of a humoral response reportedly being a good prognostic factor for outcome in breast cancer patients. 7 These data together with the high level of expression in tumour cells have led to a focus on MUC1 as a potential target for tumour immunotherapy.…”
mentioning
confidence: 99%